Desvendando as fontes de matéria orgânica para os sedimentos de uma área de manguezal sob a influência de macromaré: complexo estuarino de São Marcos, Maranhão, Brasil. - SEREJO, Jefferson Horley Feitosa (2018)
Coastal ecosystems are environments vulnerable to local and global change. The organic matter (OM) that reaches these environments can be retained or exported to the adjacent areas, which may cause some environmental, social and economic impacts. The use of geochemical tracers has been useful in the characterization of OM, as well as in the investigation of its sources and possible changes in the dynamics of sedimentary OM. Thus, the aim of this study is to establish the basis for qualitative and quantitative estimation of the different OM sources in a mangrove area of the São Marcos Estuarine Complex (SMEC) through elemental, isotopic and lignin phenol analysis. The study area is located in a mangrove area of the SMEC. Samples of water, sediment, seston (phytoplankton material) and mangrove leaves were collected at points within the study area, in August 2016. The physical-chemical characterization of the water was done with the aid of a multiparameter probe. Leaves of two species of mangrove and phytoplankton material (seston) were collected. The suspended particulate material was separated by tangential ultrafiltration. The bottom sediments were collected with the aid of a Van Veen dredger. A laser Diffraction Particle Size Analyzer (SALD 3101, Shimadzu) was used for grain size analysis. For elemental and isotopic determination, an Elemental Analyzer coupled to a Delta V Advantage Mass Spectrometer was used. The lignin phenols were characterized by the technique of Hedges and Ertel (1982) and Goñi and Montgomery (2000). The physical-chemical parameters evidenced the influence of marine waters and the dynamics of the tide in the study area. The predominance of fine material was observed in the region, which also presented some points with predominance of sand. The Pejrup (1988) diagram showed that the area is classified as moderate to very high hydrodynamics. The C:N ratio values and the isotopic signatures of the SPM and sediment samples indicate that the OM is composed of a mixture of terrestrial and marine sources. The local hydrodynamics is a significant factor in the composition and distribution of OM, causing a mixture of C3 type sources. Values of δ15N revealed that the area does not suffer major influences from external N sources, such as the discharge of effluents, and that variations can be related to isotopic fractionation of nitrogen and different microbial interactions. The presence of OM of terrestrial origin was evidenced in the analysis of lignin phenols. Values of the S:V and C:V ratios indicated the presence of woody and non-woody tissues of angiosperms, which was confirmed by LPVI values. However, this index revealed a higher contribution of non-woody tissues, evidencing the reactivity of the cinnamyl group. The Ac/Al ratio showed that the OM in the SPM and in the sediments, varies from well preserved to degraded. Degradation may be related to fungal activity and local hydrodynamics. Thus, it was concluded that the sedimentary organic matter of the study area consists of a mixture of autochthonous and allochthonous sources, of marine and terrestrial origin. The latter being predominantly from angiosperm tissues.